Environmental Advertising : Predicting Environmental Engagement by Exposure to Passive Media - Rice, Tehya M.; Stoeger, Shauna L. (My University, 2012)
This study looked at the gap between attitudes of associating oneself with environmental behaviors and environmental behaviors on campus. The attitudes of students were assessed to find whether passive media is a good way to increase awareness regarding these topics. This study looked at the new campus ride board, Zimride, and why students decided to join.
Color poster with text, charts, and graphs.
Keywords: Advertising--Green products; Environmental ethics; Mass media--Influence; Posters